Protocol for developing, disseminating and implementing a core outcome set for endometriosis. Issue 12 (21st December 2016) - Hirsch, Martin; Duffy, James M N; Barker, Claire; Hummelshoj, Lone; Johnson, Neil P; Mol, Ben; Khan, Khalid S; Farquhar, Cindy
Abstract : Introduction: Endometriosis is a common gynaecological disease characterised by pain and subfertility. Randomised controlled trials evaluating treatments for endometriosis have reported many different outcomes and outcome measures. This variation restricts effective data synthesis limiting the usefulness of research to inform clinical practice. To address these methodological concerns, we aim to develop, disseminate and implement a core outcome set for endometriosis engaging with key stakeholders, including healthcare professionals, researchers and women with endometriosis. Methods and analysis: An international steering group has been established, including healthcare professionals, researchers and patient representatives. Potential outcomes identified from a systematic review of the literature will be entered into a modified Delphi method. Key stakeholders will be invited to participate including healthcare professionals, researchers and women with endometriosis. Participants will be invited to score individual outcomes on a nine-point Likert scale anchored between 1 (not important) and 9 (critical). Repeated reflection and rescoring should promote whole and individual stakeholder group converge towards consensus, 'core', outcomes. High-quality outcome measures will be associated with core outcomes. Ethics and dissemination: The implementation of a core outcome set for endometriosis within future clinical trials, systematic reviews and clinical guidelines will enhance the availability of comparable data to facilitate evidence-based patient care. This study was prospectively registered with Core Outcome Measures in Effectiveness Trials Initiative; number: 691.